2001
DOI: 10.1053/jhep.2001.29202
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistologic study on the expressions of α-fetoprotein and protein induced by vitamin K absence or antagonist II in surgically resected small hepatocellular carcinoma

Abstract: Sixty-eight cases of single hepatocellular carcinoma (HCC) with less than 3 cm of diameter were immunohistochemically examined for the expressions of ␣-fetoprotein (AFP) and protein induced by vitamin K absence or antagonist II (PIVKA-II). In cancerous tissues, the expression rate was significantly higher for PIVKA-II (34 cases ␣-Fetoprotein (AFP) and protein induced by vitamin K absence or antagonist II (PIVKA-II) are well known as tumor markers of hepatocellular carcinoma (HCC), and their diagnostic usefulne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
47
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(59 citation statements)
references
References 30 publications
10
47
2
Order By: Relevance
“…The higher the AFP level, the earlier did a recurrence appear. Our data confirmed that AFP can be used as a serum marker for tumor aggressiveness [24][25][26][29][30][31][32]. This marker is correlated with the presence of histologic markers of poor prognosis, such as microscopic vascular invasion, presence of satellite nodules, or a poorly differentiated tumor [24][25][26][27].…”
Section: Discussionsupporting
confidence: 81%
“…The higher the AFP level, the earlier did a recurrence appear. Our data confirmed that AFP can be used as a serum marker for tumor aggressiveness [24][25][26][29][30][31][32]. This marker is correlated with the presence of histologic markers of poor prognosis, such as microscopic vascular invasion, presence of satellite nodules, or a poorly differentiated tumor [24][25][26][27].…”
Section: Discussionsupporting
confidence: 81%
“…Many studies (Tangkijvanich et al, 2000;Fujioka et al, 2001;Carr et al, 2007;Yamamoto et al, 2010;Saito et al, 2012) revealed that AFP levels > 400 ng/mL were indicative of larger tumor size, greater tumor numbers, a later clinical phase, bile duct invasion, vascular invasion, and a shorter median survival time. Elevated AFP-L3 levels were associated with larger tumor size, a later clinical stage, vascular invasion, poor tumor differentiation, and distant metastasis (Oka et al, 2001;Yoshida et al, 2002;Carr et al, 2007;Saito et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…These results are in agreement with Tangkijvanich et al, Fujioka et al, Debruyne and Delanghe, Yamamoto et al and Saito et al who reported an increased level of AFP in HCC patients. [22][23][24][25][26] Elevated AFP levels were associated with larger tumor size, a later clinical stage, vascular invasion, poor tumor differentiation, and distant metastasis. 27 There is a debate in defining the AFP cut off level for the diagnosis of the HCC.…”
Section: Discussionmentioning
confidence: 99%